The Impact of Quantitative Easing on Cryptocurrency - Gu, Cong; Lv, Benfu; Liu, Ying; Peng, Geng (International Journal of Economics and Financial Issues, 2021)
On March 23, 2020, the Federal Reserve Board started the ‘unlimited quantitative easing' to boost economy. After the announcement, an obvious boom in the cryptocurrency markets is observed. This research adopted an event analysis method, by analyzing the cumulative abnormal returns before and after the statement, the study confirmed that the QE announcement has a significant impact on the two most popular cryptocurrencies, Bitcoin and Ethereum. There could be several possible explanations: cryptocurrencies can be used as an inflation hedge, a ‘safe haven' for other financial asset classes, and a substitute way of transaction. While gold is also known as an inflation hedge and a safe haven, the abnormal returns of the two biggest cryptocurrencies over gold indicate that the third reason, cryptocurrencies are being favored as an alternative option for transactions, played an important role in the boom of Bitcoin and Ethereum, and the boom of them might lead to the frenzied market of other cryptocurrencies. Keywords: Bitcoin, Cryptocurrency, Quantitative easing, event analysis JEL Classifications: G15, C10, E52 DOI: https://doi.org/10.32479/ijefi.11532